Rancang Bangun E-Voting Berbasis Web Pada Organisasi Karang Taruna Kelurahan Kedurus - Nabilah, Aulia; Amrozi, Yusuf (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2019)
Decisions are one of the things that are of interest in an organization. Decisions are made with accurate consideration to produce the right solution and in accordance with what is needed. In decision making it is influenced by several aspects such as, influencing decisions to make decisions accurately. Decisions are the conclusions of those who are reached after a judgment, and decisions are seen as a process that consists of unity of interrelated activities. Information technology can help an organization or company to produce a decision. As an example of a case in the election of an organization chair, it can be done with E-Voting. E-voting which is a method of collecting and calculating votes using electronic devices, the organization can determine the chairman of the organization. With a decision support system method that is able to provide ability to solve problems. This research helps one organization, the youth organization, to elect the chairperson of the organization. This web-based e-Voting is designed simply to make it easier for users to use it for voting and counting the results of the vote.